STUDI HUBUNGAN TEGANGAN SUSUT DENGAN BATAS SUSUT PADA TANAH LEMPUNG BANDUNG - R A T I K S O, P
Shrinkage analysis for clay soil by excess water from ground need special consideration. Some cases are indicated that structures damaged a placed on clay soil also cased among other by shrinkage of ground happened. This thesis present the result of research from shrinkage pressure of Babakan Siliwangi clay, Ciwastra clay, and Batujajar clay by testing of Shrinkage Pressure. Shrinkage pressure is found by giving the pressure step by step start from 1.00 kg/cm2, 1.50 kg/cm2, 2.00 kg/cm2, and so on. As long as, the giving on air pressure, every 24 hours, the water content is measured by wighting the sampel. Air pressure is given continue until water content constant. After measuring for many times is found the constant water content, then the air pressure is raised up. This process is done more than on time until got the shrinkage limit. Decreasing of water content from liquid limit until shrinkage limit make the curve tend to linier, than if the air pressure is continued, the curve changed become bend. Shrinkage pressure is got by including the shrinkage limit in to rekted curve pressure with water content. The stress of rekted curve with water content are result of Shrinkage Pressure test, where shrinkage limit is got from ASTM D 427-B3 test as comparation of total Shrinkage limit, also be done the test with measuring Volume Changed and Water Content changed in the room of ITB Laboratories. Research result of shrinkage pressure for Babakan Siliwangi clay, Ciwastra clay, and Batujajar clay are indicated that conection between shrinkage pressure with Plasticity Indexs, Shrinkage Pressure with Activity and Shrinkage Pressure with Clay Fraction, tend to make the linier curve. From this research also got the result, that Shrinkage Pressure tend to become bigger with becoming the Soil Plasticity.